Development and Validation of a Safety Climate Scale for Manufacturing Industry - Abolfazl Ghahramani; Hamid R. Khalkhali (Elsevier, 2015)
Background: This paper describes the development of a scale for measuring safety climate. Methods: This study was conducted in six manufacturing companies in Iran. The scale developed through conducting a literature review about the safety climate and constructing a question pool. The number of items was reduced to 71 after performing a screening process. Results: The result of content validity analysis showed that 59 items had excellent item content validity index (≥ 0.78) and content validity ratio (> 0.38). The exploratory factor analysis resulted in eight safety climate dimensions. The reliability value for the final 45-item scale was 0.96. The result of confirmatory factor analysis showed that the safety climate model is satisfactory. Conclusion: This study produced a valid and reliable scale for measuring safety climate in manufacturing companies.